2020
DOI: 10.1097/md.0000000000020421
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and feasibility of levonorgestrel-releasing intrauterine device use in patients with adenomyosis

Abstract: To evaluate the efficacy and feasibility of levonorgestrel-releasing intrauterine device (LNG-IUD) use longer than 5 years in women with adenomyosis. Data were retrospectively collected from patients who were treated with LNG-IUD longer than 5 years at the Chungnam National University hospital for adenomyosis diagnosed with ultrasonography from January 2006 to November 2013. A total of 131 patients who were diagnosed with adenomyosis had treated with LNG-IUD longer than 5 years. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Localized side effects such as irregular uterine bleeding, vaginal bleeding, and vaginal discharge occurred more frequently in the LNG-IUS group. However, the incidence of all these symptoms significantly decreased after 5 years, consistent with another cohort study in which the incidence of adverse events decreased after 5 years in patients using LNG-IUS for endometriosis [22] . In the present study, systemic side effects such as mood changes, nausea, hair loss, acne, headache, and decreased bone density did not occur in the LNG-IUS group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Localized side effects such as irregular uterine bleeding, vaginal bleeding, and vaginal discharge occurred more frequently in the LNG-IUS group. However, the incidence of all these symptoms significantly decreased after 5 years, consistent with another cohort study in which the incidence of adverse events decreased after 5 years in patients using LNG-IUS for endometriosis [22] . In the present study, systemic side effects such as mood changes, nausea, hair loss, acne, headache, and decreased bone density did not occur in the LNG-IUS group.…”
Section: Discussionsupporting
confidence: 91%
“…However, the incidence of all these symptoms significantly decreased after 5 years, consistent with another cohort study in which the incidence of adverse events decreased after 5 years in patients using LNG-IUS for endometriosis. [22] In the present study, systemic side effects such as mood changes, nausea, hair loss, acne, headache, and decreased bone density did not occur in the LNG-IUS group. In our study, patients in LNG-IUS group were older than patients in EE/DRSP or dienogest group.…”
Section: Discussionsupporting
confidence: 42%
“…Even if contraception remains their main purpose, IUDs are also used for several non-contraceptive issues [ 2 ], especially with the advent of the levonorgestrel-releasing intrauterine system (LNG-IUS) device, which is considered a great treatment option for women with abnormal uterine bleeding and heavy menstrual bleeding, as well as dysmenorrhea [ 2 , 3 ]. Similarly, LNG-IUS are used for the conservative treatment of atypical endometrial hyperplasia and early endometrial cancer following hysteroscopic resection in reproductive age women [ 4 ] as well as the treatment of adenomyosis and endometriosis [ 2 ]. LNG-based IUDs are commonly used by women desiring to use local hormonal contraception [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LNG-IUD, an intrauterine version of progestin, has also been proposed to manage symptomatic adenomyosis, yielding satisfactory outcomes, but with some debate around appropriate treatment durations [ 11 , 25 , 26 , 27 , 28 , 29 , 30 ]. One clinical trial involving 47 patients reported pain relief from the sixth week after insertion, and a significant decrease in mean uterine volume by month 12 [ 28 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%
“…On the contrary, another trial demonstrated more long-term effects of the LNG-IUD against adenomyosis symptoms, as both dysmenorrhea and uterine volume remained significantly reduced after 3 years of follow-up of 94 enrolled patients [ 29 ]. A more recent retrospective study suggested that the beneficial impact of LNG-IUDs on heavy bleeding and dysmenorrhea, but not uterine volume reduction, may last up to six years post-insertion [ 30 ].…”
Section: Medical Treatment Of Adenomyosismentioning
confidence: 99%